2021
DOI: 10.3389/fvets.2021.621084
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chronic Kidney Disease Progression in Dogs With Therapeutic Management of Risk Factors

Abstract: This research was performed to describe the characteristics of the progression of naturally occurring chronic kidney disease (CKD) in dogs, together with the management of identified risk factors, following the International Renal Interest Society recommendations. Dogs diagnosed and staged with CKD, and with a longitudinal follow-up from the moment of diagnosis of up to a maximum of 730 days, were included. A total of 545 dogs that presented risk factors for the development of CKD were analyzed, out of which 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
0
12
0
2
Order By: Relevance
“…The prevalence of CKD was found in old age, which was due to renal impairment over time. Rather than old age, risk factors for CKD development were inflammatory/infectious diseases, history of anesthetic-surgical procedures, heart disease, neoplasm, endocrinopathies, and exposure to nephrotoxic drugs [ 2 ]. Canine vector-borne disease, particularly Ehrlichia spp., was associated with proteinuria [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The prevalence of CKD was found in old age, which was due to renal impairment over time. Rather than old age, risk factors for CKD development were inflammatory/infectious diseases, history of anesthetic-surgical procedures, heart disease, neoplasm, endocrinopathies, and exposure to nephrotoxic drugs [ 2 ]. Canine vector-borne disease, particularly Ehrlichia spp., was associated with proteinuria [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The previous study in cats with CKD showed that both plasma CR and UPC ratio were associated with shorter renal survival time [ 3 , 4 ]. In dogs, slow disease progression and higher survival rates were related to persistent monitoring of SDMA, renal proteinuria, and timely therapeutic management [ 2 ]. The IRIS group categorized the severity of kidney disease and proteinuria in which the upper value of plasma CR in Stage III was 5.0 mg/dL, whereas proteinuria in dogs is considered when the UPC ratio is higher than 0.5 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, CKD is known to be more prevalent in women than men (Chronic Kidney Disease in the United States, 2021States, , 2021. Geriatric (older/aged) canines made up 80.6% of all CKD cases (Perini-Perera et al, 2021). In felines, about 63% of all cats older than 10 years of age (geriatric) have CKD (Bartges, 2012).…”
mentioning
confidence: 99%